Strategic Management Accounting of Company Costs - Vera A. Manyaeva; Vladimir A. Piskunov; Vladimir P. Fomin (International Review of Management and Marketing, 2016)
The article considers conceptual approaches to the formation of accounting integrated information flow of strategic company management. The comparative characteristic of strategic and operational management accounting is given. The authors suggest their own definition of strategic management accounting as a component of the management function “accounting” and the mechanism of its realization. They also point out its goal and tasks. The systems of strategic management costs accounting are analyzed they form accounting and integrate information flow to develop and realize company strategy. On the basis of Activity Based Costing Method the methodology of strategic management accounting of company costs in the process-oriented management structures is suggested. The authors suggest six stages in Activity Based Costing Method and define their contents.